Dependency in Chile. Advances and Challenges [Panorama de la Dependencia en Chile: Avances y Desafíos] - Villalobos-Dintrans, P (Sociedad Medica de Santiago, 2019)
Chile is facing a process of rapid aging which poses several challenges. Among these challenges is the increase of dependency in the population. Despite its relevance, the topic has not been prioritized in the agenda. One explanation for this low-priority is the lack of information on the concept of dependency. This article shows that, in fact, no consensus exists in Chile on how to define and measure dependency. Additionally, it provides an updated estimation of dependency in the country, aiming to foster further debate on the topic. © 2019, Sociedad Medica de Santiago. All rights reserved.